2021
DOI: 10.1029/2020jd034481
|View full text |Cite
|
Sign up to set email alerts
|

Examining CO2 Model Observation Residuals Using ACT‐America Data

Abstract: background conditions. Results revealed systematic differences in atmospheric transport, most pronounced in the warm and cold sectors of synoptic systems, highlighting the importance of transport for 2 CO E residuals. While CT could reproduce the principal 2 CO Edynamics associated with synoptic systems, WRF showed a clearer distinction for 2 CO E differences across fronts. Variograms were used to quantify spatial correlation of residuals and showed characteristic residual length scales of approximately 100-30… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Using airborne in situ measurements of CO 2 fields obtained during the ACT‐America RFs, Gerken et al. ( 2021 ) exploited the performance of both mesoscale (WRF‐Chem) and global scale (CT) models using identical surface fluxes and found reasonable agreement with observations in all four seasons. Additionally, for frontal RFs, Zhang et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using airborne in situ measurements of CO 2 fields obtained during the ACT‐America RFs, Gerken et al. ( 2021 ) exploited the performance of both mesoscale (WRF‐Chem) and global scale (CT) models using identical surface fluxes and found reasonable agreement with observations in all four seasons. Additionally, for frontal RFs, Zhang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, using ground-based XCO 2 measurements at TCCON site (Park Falls, Wisconsin), Keppel-Aleks et al (2012) found that XCO 2 variability even at one location were primarily driven by combined impact of regional-scale fluxes and atmospheric dynamics and also attributed the large-scale gradients of XCO 2 to synoptic-scale meteorological processes. Using airborne in situ measurements of CO 2 fields obtained during the ACT-America RFs, Gerken et al (2021) exploited the performance of both mesoscale (WRF-Chem) and global scale (CT) models using identical surface fluxes and found reasonable agreement with observations in all four seasons. Additionally, for frontal RFs, Zhang et al (2022) also found that OCO-2 MIP models were capable of simulating observed CO 2 frontal contrasts with varying degrees of success in summer and spring, and frequent underestimation of frontal contrasts in winter and autumn.…”
Section: Overall Model-data Intercomparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…ACT‐America measurements helped to quantify atmospheric transport uncertainties (Davis et al., 2021; Feng et al., 2019; Gerken et al., 2021; Zhang et al., 2022). Within the ACT‐America project, five airborne campaigns across three regions in the Eastern and Midwestern United States were conducted to study the transport and fluxes of atmospheric carbon dioxide and methane (Pal & Davis, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Parazoo et al (2008) used combinations of simulations and observations to decompose the components of the PBL 𝐴𝐴 CO2 budget in the midlatitudes and found that the horizontal advection contributes to 60%-70% of 𝐴𝐴 CO2 daily variations on average in PBL, and thus dominates the variability seen in frontal gradients of 𝐴𝐴 CO2 . ACT-America measurements helped to quantify atmospheric transport uncertainties (Davis et al, 2021;Feng et al, 2019;Gerken et al, 2021;Zhang et al, 2022). Within the ACT-America project, five airborne campaigns across three regions in the Eastern and Midwestern United States were conducted to study the transport and fluxes of atmospheric carbon dioxide and methane .…”
mentioning
confidence: 99%